Activated nanolithia as an effective prelithiation additive for lithium-ion batteries. Issue 16 (12th April 2023) - Zhang, Jingxi; Chen, Xi; Shao, Gang; Wang, Hailong; Dong, Yanhao; Wang, Chang-An
Abstract : Mechanically activated nanolithia can be fully decomposed during the first charge half-cycle and offers a high prelithiation capacity up to 1200 mA h g −1 at 4.3 V ( vs. Li + /Li) upper cutoff voltage. Abstract : A crucial issue limiting the cycle life of practical lithium-ion batteries (LIBs) is the formation and growth of solid electrolyte interphases (SEIs) as well as other side reactions at the electrode–electrolyte interfaces that consume the lithium reservoir in the first cycle and over extended cycling. Prelithiation is an effective strategy to offset the lithium loss and extend the cycle life. Full delithiation of lithia provides 1794 mA h g −1 charge capacity, making it a promising prelithiation additive. However, its practical application is hindered by the sluggish decomposition kinetics. Here we reported mechanically activated nanolithia that can be fully decomposed during the first charge half-cycle and it offers a high prelithiation capacity up to 1200 mA h g −1 at 4.3 V ( vs. Li + /Li) upper cutoff voltage. The facile kinetics is enabled by the construction of a defect-rich Li2 O–LiCoO2 nanocomposite, which facilitates the charge transfer and the irreversible lattice oxygen redox of the nanolithia. The construction of such a nanocomposite can use cycled LiCoO2 from waste batteries as the raw material, which is economically feasible. Using the nanolithia prelithiation additive, we successfully compensated the irreversible Li loss of graphite‖LiFePO4 full cells and obtained a 28.5% higher initial discharge capacity and 43.9% higher capacity retention over 100 cycles.